(untitled) (Applied Biological Research, 2023)
An experiment was conducted at the Punjab Agricultural University, Ludhiana, India, for 2 years (2019-20 and 2020-21), to study the genetic variability, heritability, correlation and path coefficient analysis in 28 genotypes of Asiatic carrot under 8 environments. The experiment was laid out in RBD with three replications. The analysis of variance showed that the genotype’s mean sum of squares was significant for all the traits studied, indicating that significant variation existed among them. A wide range of variation existed for average root length, root weight, root diameter, core diameter and root shoot ratio i.e., 14.5- 21.0 cm, 40.9-77.8 g, 2.2-2.7 cm, 0.93-1.56 cm and 0.86 to 1.29, respectively. The average marketable yield of genotypes ranged between 365.55 to 584.55 q ha-1. Vegetative traits like shoot length varied from 42.0-64.7 cm, shoot weight from 44.71-80.14 g, and the number of leaves from 5.4 -7.2 among all genotypes. The magnitude of phenotypic coefficient of variation was greater than the corresponding genotypic coefficient of variation for all the traits indicating that trait expression is environmentally influenced. Root-shoot ratio, shoot length, number of leaves, root length, and root diameter all have exhibited highest heritability and moderate genetic advance that suggested additive gene action. Strong character association of root length, root diameter and root weight with marketable yield suggested as selection criteria for higher yield.